Tingkat Kesukaan Dendeng Sapi Substitusi Nangka Muda dengan Lama Pengeringan yang Berbeda - Yunda Maymanah Rahmadewi; Brenda Margaretha Lestari; Nur Nisrina Raihan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
The purpose of this study was to determine the level of preference for beef jerky from a mixture of beef and young jackfruit dried at different times and assessed from the level of preference on sensory attributes of color, aroma, texture, taste and overall preference. This study used a completely randomized design (CRD) with different drying time variables, namely 20, 25 and 30 hours. Data analysis in this study was obtained from the results of the organoleptic assessment of the panelists' preference for beef-jackfruit jerky which differed based on drying time. Data were analyzed using analysis of variance (Analysis of Variant), the organoleptic assessment results which had a significant effect followed by the Fisher's LSD (Least Significant Difference) test at the 95% confidence level (?=0.05). Dried young beef-jackfruit jerky for 20 hours had the highest average preference value on the texture attribute (3.7). The highest average preference values for color (3.65) and aroma (3.8) were found in the dried beef jerky for 25 hours, while the dried beef jerky for 30 hours had the highest average preference value on the attributes of taste and overall preference. The different drying times resulted in significant differences in the average preference level of the texture attributes only.